KASUS DISKRIMINASI ROKOK KRETEK INDONESIA OLEH AMERIKA SERIKAT - Muhammad Farris Ghondur Siregar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2023)
Indonesia officially filed an issue on the United States following the declaration of the Family Smoking Prevention and Tobacco Control Act of 2009, Public Law 111-31. The act forced a prohibition on all clove cigarettes, except menthol cigarettes. Indonesia saw this as discrimination towards their tobacco in the United States cigarette market. As the biggest exporter of clove cigarettes in the United States, Indonesia will experience a considerable loss because of the new act. On June 2010, Indonesia requested the establishment of the Panel in the Dispute Settlement Body (DSB) of the World Trade Organizations (WTO), in the hope of settling the issue with the United States. The goal of this research is to understand how Indonesia might be affected by the policy that is seen as discriminating towards its kretek cigarettes by the United States.